2002
DOI: 10.1182/blood-2002-01-0294
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of unrelated donor umbilical cord blood in 102 patients with malignant and nonmalignant diseases: influence of CD34 cell dose and HLA disparity on treatment-related mortality and survival

Abstract: The potential benefits of unrelated donor marrow transplantation are offset by the immunologic complications of graft-versus-host disease (GVHD) and infection. Therefore, we used cryopreserved umbilical cord blood (UCB) as a strategy to reduce the risks of GVHD and treatment-related mortality (TRM) and improve survival. Data on 102 patients (median age 7.4 years) who received transplants between 1994 and 2001 for the treatment of malignant (n = 65; 68% were high-risk patients) and nonmalignant (n = 37) disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
465
7
11

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 933 publications
(506 citation statements)
references
References 36 publications
23
465
7
11
Order By: Relevance
“…By combining these peptides with existing HSC culture protocol, we confirmed that KS-13 and modified-KS-13 increased the number of CD34 + /CD38 − HSCs over 50-fold within several days. Transplantation of higher numbers of CD34 + HSCs reportedly improves clinical outcomes [626364], and our results showed that peptides might provide new aspect to ameliorate current method for ex vivo HSC expansion.…”
Section: Introductionmentioning
confidence: 78%
“…By combining these peptides with existing HSC culture protocol, we confirmed that KS-13 and modified-KS-13 increased the number of CD34 + /CD38 − HSCs over 50-fold within several days. Transplantation of higher numbers of CD34 + HSCs reportedly improves clinical outcomes [626364], and our results showed that peptides might provide new aspect to ameliorate current method for ex vivo HSC expansion.…”
Section: Introductionmentioning
confidence: 78%
“…This is unfortunate given that cell dose is one of the main predictive factors for CBT outcomes [26–28]. Transplantation of two CB units has been introduced by investigators from the university of Minnesota to increase the cell dose infused [13, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Data, mostly from the single UCB transplantation setting, support the use of donor specific anti-HLA antibodies, 16 high resolution HLA-matching, 17 matching at HLA-C, 18 CD34 + cell dose, 7,8,19,20 and cell viability 8 to refine UCB unit selection. However, these data are not always reproducible in the double UCB focused studies.…”
Section: Discussionmentioning
confidence: 99%